THE EFFECT OF PREFERENTIAL TRADE AREAS (PTAs) IN THE PERSPECTIVE OF REGIONALISM: THE CASE OF ASEAN - Abdurrahman Al-Faqiih (Dauliyah Journal of Islamic and International Affairs, 2016)
The issue of regionalism particularly in the matter of preferential trade area is not an old fashion debate, but it becomes a prominent feature and a popular tool for global trading system. However, it does not mean that the regionalism might always bring benefit for any actor especially in terms of every national interest in the region. This paper would elaborate the effect of preferential trade area (PTAs) establishment on the economic interest of ASEAN countries member. Through literature study, this paper concludes that the PTAs produce many positive benefits for the ASEAN countries member. The flexibility of partnerships and coverage selection under PTAs has helped ASEAN solve the crisis and increase efficiency as well as stimulate the main goal of global fair trade by expanding economic linkages. Thus, it could be said that PTAs enhance the multilateralism under the WTO system